Stretchable electrically conductive polymer nanocomposites - Lai, Guan Ming (2015)
Due to the rising interest on graphene in recent years, a lot of efforts were done to improve the synthesizing method of this material. It is worth to know that low-cost and simple processes normally produced low quality graphene while high quality yields required larger amount of money and accompanied with low production efficiency. In this experiment, a newly inspired, budget yet convenient preparation method was employed. Graphite was directly exfoliated with the assistance of alkali lignin (AL) in aqueous solution through sonication. AL can exist as negatively charged molecules in the dispersion. The π-π stacking promoted the interaction between AL and graphene, at the same time, caused a negative charge layer to be formed on graphene surface. The repulsive force exerted can help to repel layers in graphite away from each other and served as a stabilizer to prevent aggregation of freshly formed graphene. The success of this method was proven by the characterization of graphene with X-ray diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR). Attentions on graphene extended further when it was reported that graphene based polymer nanocomposite can exhibit better combination of electronic and mechanical properties which exceed its constituent materials. Previous studies where graphene nanofillers were infused into polymer matrix had proven successes in enhancing the electrical conductivity of the matrix. However, at present stage, very little work was done to observe the change in ductility and electrical conductivity of nanocomposites with elastomer existed as a minor component within the samples. Therefore, another main focus of this work was to study the possibility of preparing a stretchable electrically conductive nanocomposite by adding elastomer, in this case, polyurethane (PU) at lower proportion with respect to graphene and analyze how different composition of PU would affect the electronic and mechanical properties in such system. Four point probe resistivity measurement and Dynamic Mechanical Analysis (DMA) were employed to study the electronic and mechanical properties of each sample with different PU content. It was noticed that PU can affect the properties of nanocomposites to quite a large extent. The changes became bigger and more obvious when a reduction of 52%, 90% and 97% in electrical conductivity was observed as the amount of PU added increased. On the other hand, the achievable maximum strain recorded for each sample was enhanced when the composition of PU increased in the similar manner.